1996
DOI: 10.1002/(sici)1097-0061(19960915)12:11<1135::aid-yea11>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

TheS. cerevisiae nitrogen starvation-induced Yvh1p and Ptp2p phosphatases play a role in control of sporulation

Abstract: Starvation for nitrogen in the absence of a fermentable carbon source causes diploid Saccharomyces cerevisiae cells to leave vegetative growth, enter meiosis, and sporulate; the former nutritional condition also induces expression of the YVH1 gene that encodes a protein phosphatase. This correlation prompted us to determine whether the Yvh1p phosphatase was a participant in the network that controls the onset of meiosis and sporulation. We found that expression of the IME2 gene, encoding a protein kinase homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 59 publications
2
37
0
1
Order By: Relevance
“…The transcription profile revealed that rapamycin does not cause yeast growing in rich media to appear nitrogen-starved. Two genes that are normally induced by nitrogen starvation, YVH1 and PTP2 (33), are repressed or unchanged, respectively, after treatment with rapamycin. Also, of 52 genes of unknown function that were shown to be sensitive to nitrogen starvation (34), only 19% (10 genes) were appropriately modulated in the response to rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription profile revealed that rapamycin does not cause yeast growing in rich media to appear nitrogen-starved. Two genes that are normally induced by nitrogen starvation, YVH1 and PTP2 (33), are repressed or unchanged, respectively, after treatment with rapamycin. Also, of 52 genes of unknown function that were shown to be sensitive to nitrogen starvation (34), only 19% (10 genes) were appropriately modulated in the response to rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…This interaction is reminiscent of the yeast DSP Yvh1 and the tyrosine phosphatase Ptp2, which have little effect when mutated alone, but double mutants are sporulation defective (Park et al, 1996). As there are five additional MKPs in the Drosophila genome (Morrison et al, 2000), negative regulation of ERK by a combinatorial network of those phosphatases will probably reveal high redundancy as well.…”
Section: Dmkp3 Is a Negative Regulator Of The Ras/mapk Pathwaymentioning
confidence: 99%
“…In the model yeast Saccharomyces cerevisiae, YVH1, one of the DSPs, was first identified as a vaccinia VH1 homologue (Guan et al, 1992). Deletion of YVH1 in S. cerevisiae causes defects in vegetative growth (particularly at lower temperatures), sporulation and glycogen accumulation, and transcription of YVH1 is induced by low temperature and nitrogen starvation (Beeser & Cooper, 2000;Guan et al, 1992;Park et al, 1996;Sakumoto et al, 1999Sakumoto et al, , 2001). However, even in S. cerevisiae, the exact function of YVH1 remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%